PRÁTICAS LINGUÍSTICAS COMUNITÁRIAS PRESENTES EM CONTEXTO ESCOLAR BI/MULTILÍNGUE: UMA ANÁLISE DE PRODUÇÕES ACADÊMICAS (2009 - 2020) - SCHWAB, PATRICIA GROCOSKI (2022)
This dissertation, based on the theoretical assumptions of field education (SCHEWENDLER, 2005; CALDART, 2012) and the concepts of language, culture and bi-multiculturalism (PAREJA, 2013; MUSSOLIN; BENTES, 2006; KRAUSE-LEMKE, 2010) has as main objective to analyze what is the type of approach adopted by academic papers that deals with community linguistic practices present in a bi/multilingual school context in the Southeast region of Paraná State, focusing on recent academic productions (from 2009 to 2020). The methodology used is qualitativ, with research based on bibliographic and documentary data. To this, five recent academic productions are taken, from which it is analyzed: a) if education in the country side presents a correlation with the cultural identity of the communities of the Prudentópolis/PR city; b) if the presence and use of different languages in the school context is taken into account in the research; c) if academic papers refer to the roles assigned to the languages of the context in the school and in the community. The results show the reality of community bi/multilingual linguistic practices occur in a marked way, being easily noted in the school context.